ICDAR 2011 Document Image Binarization Contest (DIBCO 2011) - Pratikakis, I.; Gatos, B.; Ntirogiannis, K. (2011 International Conference on Document Analysis and Recognition, 2011)
DIBCO 2011 is the International Document Image Binarization Contest organized in the context of ICDAR 2011 conference. The general objective of the contest is to identify current advances in document image binarization for both machine-printed and handwritten document images using evaluation performance measures that conform to document image analysis and recognition. This paper describes the contest details including the evaluation measures used as well as the performance of the 18 submitted methods along with a short description of each method.